Analisis Bibliometrik Motivasi Pelayanan Publik : Identifikasi Kesenjangan Ilmiah - Berthanila, Rethorika; Marthalena, Marthalena; Nurhakim, Fatwa (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2025)
Public service motivation (PSM) research has increased significantly in various disciplines, especially public administration and public sector management. This study uses bibliometric analysis based on data from Scopus to identify the main trends, author contributions, and scientific gaps in PSM research from 1996 to 2023. The analysis results show that PSM remains a major topic in public administration research, with a significant increase in publications since 2006. The most dominant keywords include public administration, work engagement, job satisfaction, and transformational leadership. Furthermore, this study revealed that most PSM research focuses on employee engagement and job satisfaction, while aspects such as the integration of PSM with public service values (PSV) and public service ethos (PSE) are still rarely explored. In addition, citation network analysis shows that Indiana University Bloomington and Utrecht University are the most influential institutions in this research. This study contributes by providing an updated bibliometric mapping, identifying recent research trends, and offering recommendations for future studies related to innovations in public service motivation models.